Debt and development crises in Latin America the end of an illusion - Griffith-Jones, Stephany; Sunkel, Osvaldo (Oxford, [England] Clarendon Press, 1986)
"In the early 1980s, widespread debt crises erupted simultaneously in most Latin American countries. This book examines the link between these debt problems and a more profound and longer-term growth and development crisis, both in Latin America and in the industrialized countries. The authors argue that the debt and development crises have common origins and causes and propose measures to treat both crises, including fundamental changes in the policies of developed countries, the international financial system, and national development strategies of the developing countries, and a radical solution to the debt problem."--Publisher's description.
Includes bibliographical references and index.
Keywords: Debts, External -- Latin America; International finance; Latin America -- Economic conditions -- 1982- .